The Hyperspherical Harmonics Method: A Tool for Testing and Improving Nuclear Interaction Models - Marcucci, Laura E.; Dohet-Eraly, Jérémy; Girlanda, Luca; Gnech, Alex; Kievsky, Alejandro; Viviani, Michele (Frontiers in Physics, 2020)
The Hyperspherical Harmonics (HH) method is one of the most accurate techniques to solve the quantum mechanical problem for nuclear systems with a number of nucleons A4. In particular, by applying the Rayleigh-Ritz or Kohn variational principle, both bound and scattering states can be addressed, using either local or non-local interactions. Thanks to this versatility, the method can be used to test the two- and three-nucleon components of the nuclear interaction. In the present review we introduce the formalism of the HH method, both for bound and scattering states. In particular, we describe the implementation of the method to study the A=3 and 4 scattering problems. Second, we present a selected choice of results of the last decade, most representative of the latest achievements. Finally, we conclude with a discussion of what we believe will be the most significant developments within the HH method for the next five-to-ten years.